Research Data Management and Crowdsourcing Personal Histories - Catherine Conisbee (Journal of Open Humanities Data)
Drawing on experiences of the University of Oxford’s Sustainable Digital Scholarship (SDS) service and the World War Two crowdsourcing project ‘Their Finest Hour’, this paper explores how institutional digital repositories (such as the SDS platform) can be successfully leveraged to publish and sustainably host crowdsourced (‘warm-data’) collections beyond their funding period. The paper examines the challenges in applying FAIR (Findable, Accessible, Interoperable, Reusable) principles to a collection containing first-hand testimonies and digitised objects of significant sentimental value, addressing both practical and ethical considerations, including the management of copyright, handling of sensitive material, use of AI tools and adherence to good research data management practices, with limited resources. Reflecting on the importance of a caring approach to data stewardship, the paper examines how the ethos of the Their Finest Hour project, and its commitment to honouring contributors and their families, led organically to an alignment with CARE (Collective Benefit, Authority to Control, Responsibility, Ethics) principles, originally developed for Indigenous data governance. It also explores the potential for the wider application of CARE principles for crowdsourced collections such as the Their Finest Hour Online Archive, while acknowledging and respecting the origins of this framework. Lastly, it offers some practical ‘lessons learned’ to help GLAM and Higher Education professionals working with crowdsourced collections and personal histories to navigate some of the research data management challenges that they may encounter, while also highlighting the importance of understanding FAIR and CARE principles and how they can be applied to these types of data collections.